2010
DOI: 10.1002/chem.200903044
|View full text |Cite
|
Sign up to set email alerts
|

General Method for the 11C‐Labeling of 2‐Arylpropionic Acids and Their Esters: Construction of a PET Tracer Library for a Study of Biological Events Involved in COXs Expression

Abstract: Cyclooxygenase (COX) is a critical enzyme in prostaglandin biosynthesis that modulates a wide range of biological functions, such as pain, fever, and so on. To perform in vivo COX imaging by positron emission tomography (PET), we developed a method to incorporate (11)C radionuclide into various 2-arylpropionic acids that have a common methylated structure, particularly among nonsteroidal anti-inflammatory drugs (NSAIDs). Thus, we developed a novel (11)C-radiolabeling methodology based on rapid C-[(11)C]methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…11 C-KTP-Me is promptly and almost completely hydrolyzed to acid form, 11 C-KTP, in rat brain within 5 min after the intravenous injection and can be used with PET to visualize time-dependent changes in COX-1 in activated microglia during neuroinflammatory processes (7,8). This finding provided evidence that COX-1 plays a critical role in microglial activation during acute neuroinflammation in vivo.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…11 C-KTP-Me is promptly and almost completely hydrolyzed to acid form, 11 C-KTP, in rat brain within 5 min after the intravenous injection and can be used with PET to visualize time-dependent changes in COX-1 in activated microglia during neuroinflammatory processes (7,8). This finding provided evidence that COX-1 plays a critical role in microglial activation during acute neuroinflammation in vivo.…”
mentioning
confidence: 88%
“…According to a previous report, 11 Clabeled ketoprofen methyl ester as a racemate ((RS)-11 C-KTP-Me) was synthesized by the reaction of 11 C-CH 3 I and (3-benzophenyl)acetic acid methyl ester in the presence of bases (7). The radioactivity of the final samples including (RS)-11 C-KTP-Me was 2.5-4.0 GBq, and the specific activity was 30-50 GBq/mmol.…”
Section: Radiochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…35 Consequently, we elaborated rapid 11 C labeling using the reaction of [ 11 C]CH 3 I and an enolate intermediate generated from the corresponding ester under basic conditions, 36 followed by one pot hydrolysis to convert to 11 C incorporated acid as [ [ 11 C]loxoprofen, and their corresponding esters. Notably, we found that methyl esters were particularly useful as pro radioprobes for a study of neuroinfl ammation in the brain.…”
Section: Dmentioning
confidence: 99%
“…The microPET studies of rats with lipopolysaccharide (LPS) induced brain infl ammation clearly showed that the radioactivity of PET probes accumulated specifi cally in the infl amed region (Figure 7), giving the fi rst successful example of the in vivo molecular imaging of neuroinfl ammation by the noninvasive PET technology. 35 A metabolite analysis in the rat brain revealed that the methyl ester intravenously administrated was initially taken up in the brain and then underwent the hydrolysis to form a pharmacologically active form of the corresponding acids. 35 Hence, we succeeded in the general 11 C labeling of 2 arenylpropionic acids and their methyl esters as PET probes of NSAIDs to construct a potentially useful PET probe library for the in vivo imaging of infl ammation involved in COX s expression.…”
Section: Dmentioning
confidence: 99%